2005
DOI: 10.2165/00139709-200524010-00001
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Adverse Health Effects of Dental Amalgam

Abstract: There is significant public concern about the potential health effects of exposure to mercury vapour (Hg(0)) released from dental amalgam restorations. The purpose of this article is to provide information about the toxicokinetics of Hg(0), evaluate the findings from the recent scientific and medical literature, and identify research gaps that when filled may definitively support or refute the hypothesis that dental amalgam causes adverse health effects. Dental amalgam is a widely used restorative dental mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 74 publications
1
77
0
5
Order By: Relevance
“…34 The authors noted that many studies report positive correlations between the number of amalgam restorations (or surfaces) and urine mercury concentrations in non-occupationallyexposed individuals. The authors also reported, however, that these correlations do not prove that increased urine mercury concentrations cause adverse health effects.…”
Section: Berglund and Molinmentioning
confidence: 99%
“…34 The authors noted that many studies report positive correlations between the number of amalgam restorations (or surfaces) and urine mercury concentrations in non-occupationallyexposed individuals. The authors also reported, however, that these correlations do not prove that increased urine mercury concentrations cause adverse health effects.…”
Section: Berglund and Molinmentioning
confidence: 99%
“…A recent review uncovered no convincing evidence pointing to any adverse health effects that are attributable to dental amalgam restorations besides hypersensitivity in some individuals [16]. However, a study on 18 cadavers showed significantly higher total mercury levels in subjects with a greater number of occlusal amalgam surfaces compared with those with fewer occlusal amalgams in all types of tissues [17].…”
Section: Discussionmentioning
confidence: 99%
“…The question remains, however, whether metallic mercury exposure from dental amalgams is the cause of adverse health effects, including multiple sclerosis, autism, CNS and renal damage, chronic fatigue, memory impairment and depression. These conditions and their etiology have been studied extensively and risk factors are well defined (see the review article by Brownawell et al 2005).…”
Section: Adverse Effects In Individuals With Amalgam Restorationsmentioning
confidence: 99%